16‐3: High‐end Displays Applications by Micro‐LEDs. Issue 1 (25th September 2020) - Lin, Chien-chung; Fang, Yen-Hsiang; Kuo, Wei-Hung; Liang, Kai-Ling; Tseng, Jie Ting; Hu, Pin Hao; Lin, Mao Chi; Wu, Chih-I
Abstract : As the request for high resolution display is rising, it is imperative to develop the corresponding micro‐LED technology to match this demand. In this paper, we demonstrate our latest efforts on color conversion patterning and seamless tiling for glass substrate. The color conversion can be achieved by colloidal quantum dots and we have patterns less than 10 microns deposited on LED chips. A continuous operation of more than 100 hours without linewidth broadening can be observed if quantum dots are well protected. The glass cutting technique was accomplished by optimized pulsed laser beam. The heat affected zone can be reduced from 100 to 15 microns. The resultant seamless tiling of the MicroLED on glass substrate can be demonstrated. These techniques can be useful for next generation of high end displays..